The uncertain fate of a wandering appendicolith: personal experience and literature review - Cavallaro, Andrea; Zanghì, Antonio; Di Mattia, Paolo; Sanfilippo, Filippo; La Via, Luigi; Riccioli, Giordana; Cappellani, Alessandro; Tiralongo, Kenya (Frontiers in Surgery, 2025)
IntroductionRetained appendicoliths are an uncommon but clinically relevant complication of appendectomy, particularly in cases of perforated appendicitis. Migration of the appendicolith into the peritoneal cavity or liver may lead to persistent or recurrent abscess formation.Case descriptionWe present the case of a 29-year-old male with recurrent hepatic abscesses following laparoscopic appendectomy. Initial CT and MRI imaging revealed calcified components within the liver consistent with a migrated appendicolith. Despite percutaneous drainage and antibiotic therapy, the patient experienced relapse. Definitive resolution was achieved through laparoscopic hepatic resection and removal of the retained appendicolith.DiscussionThis case highlights the diagnostic challenges and potential complications associated with retained appendicoliths. Imaging plays a crucial role in identification and management. While conservative approaches may be attempted, surgical retrieval is often required to prevent recurrent infections.ConclusionRetained appendicoliths should be considered in the differential diagnosis of hepatic abscesses following appendectomy. Timely diagnosis and complete removal are essential to avoid long-term morbidity.